EFEK METODE BRAINSTORMING TERHADAP TINGKAT PENGETAHUAN DAN RASIONALITAS PENGGUNAAN OBAT SWAMEDIKASI (The Effect Brainstorming Method to Knowledge and The Rational of Self Medication) - Fauziningtyas, Rista; Diantami, Aldini Yunita Mia; Makhfudli, Makhfudli (JURNAL NERS LENTERA, 2018)
Introduction: The implementation of self-medication may be a source of medication error due to the limited knowledge of the community about the drug and its use. Based on the preliminary study, the majority of people in the Working Area of Puskesmas Desa Soso, Kecamatan Gandusari, Kabupaten Blitar, was used the self-medication inaccurately. This study was purposed to analyze the effect of brainstorming on the level of knowledge and rationality of drug use. Method: This study was used in experimental design with a Quasy-experimental approach and purposive sampling technique. Independent variables is Brainstroming and dependent variabel are knowledge and rationality of drug usage. This sample are 30 respondents that divided into two groups, there are control group and experimental group. The data were collected using questionnaires and analyzed using Wilcoxon-Mann Whitney test with p-value